The a to Z of the United States-Mexican War - Moseley, Edward H.; Clark, Paul C. (Rowman & Littlefield Publishers, 2009)
The first reference work of its kind, this volume on the United States-Mexican War encompasses the decade of the 1840s, focusing on the war years of 1846-1848. More than a dozen maps were drawn for this book, some of which depict major regions and localities over which armies of both nations moved great distances to position for battle, and others that depict major battlefields from the first engagement to the last. The narrative overview paints a broad picture of the war for both historians desiring a review before continuing research and for the interested layperson unfamiliar with the war and in search of an overview of the entire period. The dictionary itself contains hundreds of thoroughly researched entries describing the war's personalities, battles and campaign trails, armaments, support systems, political factions involved in the conflict in both nations, and an array of other topics related to the war. This reference also includes illustrations of the central figures of the conflict, a detailed chronology, and a bibliography of traditional and contemporary sources useful to the professional scholar, student, and amateur historian.